Thinking Strategically about Inclusion in Museums (interview with David Fleming) - Carvalho, Ana (2017)
Inclusion has been a key word in National Museums Liverpool – NML (eight museums altogether), underlined in its mission statement: "To be the world’s leading example of an inclusive museum service".